(untitled) (ACTA MEDICA PERUANA, 2020)
Objective: to compare the sale price of essential drugs used in the management and therapy of COVID-19 in public and private pharmacies in Peru. Also, to assess the cost per person of drug therapy for both mild and severe cases. Materials and methods: this is a cross-sectional study using data reported by public and private pharmacies in Peru. Drug prices are presented as median values and they were compared using the non-parametric Kruskal-Wallis test. Also, costs per person and drug accessibility for treating mild and moderate cases were estimated. Results: drugs used when treating mild cases of COVID-19, such as azythromycin, hydroxichloroquine, ivermectin, and paracetamol had median prices between S/ 0.04 (US 0.011) and S/ 23.81 (US 6.71) in public pharmacies, while the same compounds cost between S/ 1.00 (US 0.28) and S/ 36.00 (US 10.15) in private pharmacies. On average, drug prices in private pharmacies are 11 times higher compared to those in public pharmacies. Costs for (COVID-19) therapy in public pharmacies are more accessible compared to those found in private pharmacies, particularly for drugs used for more severely affected patients. Therapy regimens for mild cases require spending 1 to 4 days of the minimum daily wages, while therapy for severe cases (of COVID-19) may require up to 64 days of the minimum daily wages in private pharmacies. Conclusions: pharmacological treatment for COVID-19 represents an important expense for the public health system and for families through out-of-pocket expenses. It is urgent to design and implement regulatory measures aiming to improve the access to drug therapy (for Covid-19) in order to have drugs sold at accessible prices.